2013
DOI: 10.1186/1824-7288-39-76
|View full text |Cite
|
Sign up to set email alerts
|

Focal epilepsy with ictal abdominal pain: a case report

Abstract: Focal epilepsy with ictal abdominal pain is an unusual partial epilepsy characterized by paroxysmal episodes of abdominal or visceral pain, disturbance of awareness and electroencephalographic abnormalities. We describe a new case of ictal abdominal pain in which gastrointestinal complaints were the only manifestation of seizures and review the previously described pediatric patients. In our patient clinical findings, ictal EEG abnormalities, and a good response to antiepileptic drugs allowed us to make a diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Previously, the diagnosis of AE was based upon an abnormal EEG (Devore et al, 1955), including epileptiform discharges (Papatheophilou et al, 1972;Garcia-Herrero et al, 1998) and "dysrhythmias" (Bental et al, 1967), with only a few reports on ictal EEG (Matsuo, 1984;Cerminara et al, 2013;Aljaafari et al, 2018). Previously, studies on patients diagnosed with AE focused on temporal epileptiform abnormalities (Moore, 1962;Zinkin and Peppercorn, 2005).…”
Section: Video-eeg Monitoringmentioning
confidence: 99%
“…Previously, the diagnosis of AE was based upon an abnormal EEG (Devore et al, 1955), including epileptiform discharges (Papatheophilou et al, 1972;Garcia-Herrero et al, 1998) and "dysrhythmias" (Bental et al, 1967), with only a few reports on ictal EEG (Matsuo, 1984;Cerminara et al, 2013;Aljaafari et al, 2018). Previously, studies on patients diagnosed with AE focused on temporal epileptiform abnormalities (Moore, 1962;Zinkin and Peppercorn, 2005).…”
Section: Video-eeg Monitoringmentioning
confidence: 99%
“…3 There are no recommendations on the choice of the anticonvulsant. 2 Of the 18 pediatric cases, carbamazepine was used in 3 cases, oxcarbazepine in 2 cases, valproate in 2 cases, phenytoin in 1 case, phenobarbitone in 3 cases, both phenytoin as well as phenobarbitone in 2 cases, and surgical management done in 2 cases. Thirteen children became absolutely seizure free, while 2 children showed reduced frequency of seizures.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although all other forms of epilepsy may occur in infants, abdominal epilepsy (AE) has not been described younger than 1 year of age. 2 The authors speculate that the reason for this is that two out of the four diagnostic criteria of AE require that the patient himself will be able to "speak out" that he is having abdominal pain and fatigue, dizziness, headache, etc. 3 However, this is impossible for the young infants, in whom inconsolable cry is the only language of any type of discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…The syndrome has been well documented in children . However, there are very few reported cases among adults .…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study showed that epileptic pain including abdominal pain is a rare symptom of seizures in both children and adults . Despite the scarcity of described cases among adults, there are several case reports of abdominal epilepsy in children . One study involving 150 children with chronic recurrent abdominal pain found that 74% of them had abdominal epilepsy .…”
Section: Discussionmentioning
confidence: 99%